Effect of pH values on structural, optical, electrical and electrochemical properties of spinel LiMn2O4 cathode materials - Chand, Prakash (Elsevier, 2019)
In the present work, we have synthesized the spinel LiMn2O4 cathode materials via a sol-gel method at 750 C for 8 h under optimal conditions at different pH values (3, 6 and 9) and studied the effect of different pH values on the structural, optical, electrical and electrochemical properties. X-ray diffraction (XRD) analysis identified the synthesized materials as crystallized in the cubic spinel structure (Fd3m) with slight decrease in the lattice parameters. SEM exhibits the formation of a spongy and fragile network structure in the synthesized samples. An enhancement in the optical energy band (Eg) leads to the blue shift in the synthesized samples with reduced crystallite size. Cyclic voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS) investigations show that the LiMn2O4 nanostructures synthesized at pH 9 exhibit the long-term cycle constancy and a superior electrochemical reproducibility as compared to those synthesized at pH values of 3 and 6. The results revealed that pH plays a significant role in tuning the structural, optical and electrochemical properties of the LiMn2O4 cathode material, which is considered a promising substitute of cathode materials for the novel lithium-ion battery applications